Green Finance and Corporate Sustainability: Strategic Financial Management in the Era of ESG Investing - Nekky Rahmiyati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study analyzes the strategic role of green finance driven by Environmental, Social, and Governance (ESG) investing in supporting corporate sustainability. The objectives are to examine the integration of ESG criteria into financial management practices, identify challenges and opportunities in aligning corporate financial strategies with sustainable investment trends, and propose a conceptual framework for strategic financial management aimed at long-term value creation. A systematic literature review method was employed, using data from peer-reviewed journals, reports, and white papers published between 2015 and 2025 that addressed green finance, corporate sustainability, strategic financial management, and ESG. Thematic analysis and narrative synthesis were applied to identify key trends, frameworks, and best practices, with triangulation of sources ensuring validity. The findings reveal that green finance instruments such as green bonds and ESG-based investment portfolios influence corporate financial strategies by integrating sustainability metrics with traditional financial indicators. ESG adoption enhances resilience, reputation, and access to sustainable capital markets. Key challenges include regulatory inconsistency, greenwashing risks, and insufficient ESG reporting standards. This study concludes that green finance is a strategic imperative, enabling companies to balance financial performance with social value to achieve long-term sustainability.